Studies on the growth, structural and electrical properties of silicon-based heterostructure nanowires / Qian Guanghan - Qian, Guanghan (2015)

(untitled)
This work reports the investigation of Ni catalyzed Si-based nanowires grown by hot-wire chemical vapor deposition at different filament temperatures on crystal Si (c-Si) and glass substrates These nanowires include NiSi, NiSi/Si core-shell and NiSi/SiC core-shell nanowires that grown by varying the filament temperature, Tf. The NiSi nanowires were grown at lowest Tf of 1150C. At Tf of 1450C, the nanowires were structured by crystalline Si and amorphous Si which Si attributed to the core and shell of the nanowires, respectively. The nanowires exhibited NiSi/SiC heterostructure core-shell nanowires with increase in Tf to 1850C. The morphological properties of these nanowires were strongly dependent on the substrate and filament temperature. The nanowires grown on c-Si substrate showed a better alignment and a higher density as compared to the nanowires grown on glass substrate. The effect of hydrogen heat transfer by the filament temperature demonstrated a phase change from NiSi to Ni2Si with increase in filament temperature. The increasing of filament temperature enhances gas phase reactions thus generates more SiC clusters which consequently formed the SiC shell. These NiSi/SiC core-shell nanowires were structured by single crystalline NiSi and amorphous SiC respectively. The roles of the filament temperature on the growth and constituted phase change of the nanowires are discussed in detail. Last but not least, the core-shell nanowires exhibited a significant hetero-junction electrical characteristic which could be a great potential application in nano-diode devices. Keywords: Heterostructure, core-shell nanowires, HWCVD, SiC, NiSi